2020
DOI: 10.1136/bmjopen-2019-032840
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in native populations living at high altitude: a cross-sectional survey in Derong, China

Abstract: ObjectiveThe metabolic syndrome is a major risk factor for cardiovascular disease. Little information exists on the prevalence of the metabolic syndrome at high-altitude areas in China. We aimed to estimate the prevalence of metabolic syndrome and its individual components at high altitude.MethodsA cross-sectional survey of 5053 adults living in Derong from elevation of 2060 to 3820 m was carried out in 2013. Metabolic syndrome was defined according to the Chinese Diabetes Society criteria.ResultsThe overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
1
16
1
7
Order By: Relevance
“…In general, the evaluation of methodological quality showed that the two studies with the highest scores were Sherpa et al [ 10 ] and Huang et al [ 24 ] (9 and 8 points, respectively), followed by Guo et al [ 25 ], Lin et al [ 26 ], Hurtado-Arestegui et al [ 27 ] and Herrera-Enriquez, Narvaez Guerra [ 28 ] (with 7 and 6 points, respectively); and Lopez-Pascual et al [ 29 ], De Ferrari et al [ 30 ], and Miele et al [ 7 ] (5 points) on this scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the evaluation of methodological quality showed that the two studies with the highest scores were Sherpa et al [ 10 ] and Huang et al [ 24 ] (9 and 8 points, respectively), followed by Guo et al [ 25 ], Lin et al [ 26 ], Hurtado-Arestegui et al [ 27 ] and Herrera-Enriquez, Narvaez Guerra [ 28 ] (with 7 and 6 points, respectively); and Lopez-Pascual et al [ 29 ], De Ferrari et al [ 30 ], and Miele et al [ 7 ] (5 points) on this scale.…”
Section: Resultsmentioning
confidence: 99%
“…It is currently estimated that more than 400 million people worldwide reside in high-altitude areas above 1500 m above sea level (MASL) [ 24 ], representing a major physiological challenge for residents of these regions.…”
Section: Discussionmentioning
confidence: 99%
“…У жительниц Индонезии данный показатель превышает заболеваемость МС среди лиц мужского пола (46% и 28% соответственно) [24]. Однако распространенность МС в высокогорных районах Китая выше у мужчин (5,9%) в сравнении с женщинами (1,8%) [26]. У мужчин, проживающих в Нидерландах, также заболеваемость МС выше (36%), чем у женщин (24%) [24].…”
Section: факторы обусловливающие распространенность метаболического синдромаunclassified
“…В то же время в Китае МС чаще встречается у сельских жителей мужского пола, в то время как у взрослых городских жителей более распространены гипертония и ожирение. Так, распространенность МС в городе и сельской местности составила соответственно 6,6% (11,9% у мужчин и 1,5% у женщин) против 3,0% (4,6% у мужчин и 1,8% у женщин) [26]. Текущие данные другого исследования указывают на высокую распространенность МС среди сельских жителей Китая, при этом чаще данное заболевание встречается у женщин [6].…”
Section: факторы обусловливающие распространенность метаболического синдромаunclassified
“…The prevalence of MetS in European and American countries is 24.3% (23.9% in men and 24.6% in women) (5). In China, recent surveys in different age and regional populations have found that the prevalence of MetS varies from approximately 3.6 to 50.1%, with significant gender and regional differences (6)(7)(8). The relationship between MetS and PCA is still not fully established.…”
Section: Introductionmentioning
confidence: 99%